Parrot and Olivier in America [a novel] - Carey, Peter 1943- (Knopf, 2010)
Olivier is the traumatized child of aristocratic survivors of the French Revolution. Parrot is the motherless son of an itinerant English printer. They are born on different sides of history, but their lives will be connected in the United States by an enigmatic one-armed marquis.
Keywords: Geschichte 1793-1837; Aristocracy (Social class) -- France -- Fiction; French -- America -- Fiction; Voyages and travels -- Fiction; Master and servant -- Fiction; Male friendship -- Fiction; Butler; Französischer Flüchtling; Abenteuer; Adel; Amerika; Frankreich; America -- Fiction; USA; Adenture fiction; Fiktionale Darstellung; Adventure fiction